Firm Dynamics, Job Outcomes, and Productivity : South African Formal Businesses, 2010-14 - Aterido, Reyes; Hlatshwayo, Ayanda; Pieterse, Duncan; Steenkamp, Andre (World Bank, Washington, DC, 2019)
The formal private sector has a key role to play in fostering growth and reducing unemployment in South Africa—strengthening its performance is therefore critical. This paper looks at firm behaviour, firm entry and exit, job outcomes, and productivity dynamics using firm-level administrative data for South Africa. It is the first paper to benchmark employment and productivity dynamics against various comparator countries for which similar analysis has been undertaken. The paper finds that South Africa has an aged private sector with low firm dynamism and characterized by large firms that hold a large share of employment and revenue, although they are not as productive as micro firms and pay lower wages on average. The paper also finds that job creation is concentrated predominantly in incumbent firms, which are old and large, and job creation from entry and exit is negligible. The static and dynamic productivity decompositions raise a concern that although productive efficiency is gained, it is at least in part at the expense of labor. Large firms are not exploiting economies of scale, and particularly unproductive large firms may drive the weak performance of the private sector. Relatively high wages in South Africa could be partly explained by the inefficient use of labor and negative correlation between productivity and size. Likewise, these larger firms could be responsible for the negative direct impact on jobs of firms raising productivity.